Behold, America: a history of America first and the American Dream - Churchwell, Sarah Bartlett (Bloomsbury Publishing, 2018)
What does America stand for in the twenty-first century? Behold, America confronts this urgent question by looking at the story behind two of the most contentious phrases in the American political playbook: the 'American dream' and 'America first'. What do these phrases tell us about America's idea of itself? What does it mean to put America first, and what exactly are Americans supposed to be dreaming of--personal wealth, public power, racial equality, political refuge, individual freedoms? What happens when these values collide? 'America first' and the 'American dream' were born nearly a century ago and instantly tangled over capitalism, democracy and race. Invoked most recently in Donald Trump's presidential campaign, they came to embody opposing views in the battle to define the soul of the nation. Behold, America recounts the unknown history of these two expressions using the voices that helped shape that debate, from Capitol Hill to the newsroom of the New York Times, students to senators, dreamers to dissenters. As America struggles again to project a shared vision, to itself and to the world, Sarah Churchwell argues that the meanings and history of these terms need to be understood afresh so that the true spirit of America can be reclaimed. Insightful and revelatory, Behold, America overturns everything we thought we knew about the American dream, America first and the battle for the identity of modern America. -- Back cover